The Influence of Mathematical Comprehension and Connection Abilities on Students' Mathematical Representation Ability - Nurma Izzati; Mukhammad Ali Nurhidayyah (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study aims to identify the influence of mathematical understanding and mathematical connection skills on students' mathematical representation skills. This study is motivated by the low level of students' mathematical representation skills, which is thought to be influenced by limited conceptual understanding and by difficulties connecting mathematical ideas. This study uses a quantitative, correlational design with a sample of class X-1 students at SMA Negeri 1 Arjawinangun. A total of 30 students were selected through cluster random sampling. Data were collected using a validated essay test to measure mathematical understanding, mathematical connection, and mathematical representation skills, and analyzed using multiple linear regression after meeting the classical assumption tests, including normality, multicollinearity, and heteroscedasticity. The results show that mathematical understanding and mathematical connection skills have a positive and significant influence on students' mathematical representation skills, both partially and simultaneously, where mathematical understanding (β = 0.484, p < 0.05) and mathematical connection (β = 0.298, p < 0.05) significantly contribute to the dependent variable. Furthermore, the two variables simultaneously explained 99.6% of the variance in students' mathematical representation skills (R² = 0.996), indicating a very strong predictive relationship. This finding highlights the importance of strengthening students' conceptual understanding and their ability to connect mathematical ideas to improve mathematical representation skills.